Adjetivos adverbializados: anÃlise lÃxico-funcional e implementaÃÃo computacional - Daniel de FranÃa Brasil Soares (2018)
In this work, we propose a computational linguistic analysis of the so-called adverbialized adjectives (hereinafter AdjAdvs). On the one hand, we start by questioning whether AdjAdvs belong to category A(djective) or ADV(erb) and, on the other, which approach is computationally more efficient. We base our point of view according to the Lexical-Functional Grammar (LFG) (KAPLAN and BRESNAN, 1982) and implement in the XLE system (Xerox Linguistic Environment) a fragment of Brazilian Portuguese grammar (henceforth PB) capable of analyzing adjectives in adverbial use. Our implementation is based on the adaptation of a fragment of French grammar constructed by Schwarze and Alencar (2016) and deepened in FrGramm by Alencar (2017). This fragment of grammar adapted to PB serves as the basis for the implementation of two versions for a comparative analysis: G-A and G-ADV. In the first version, AdjAdvs are analyzed as adjectival category, while in the second they are analyzed as adverbial category. The implementation of G-A and G-ADV is evaluated by applying a parser to a set of 168 grammatical sentences and 286 ungrammatical sentences. After testing grammatical and ungrammatical sentence sets, G-A and G-ADV grammars processing results in XLE and the statistical analysis based on the double factor variance test, we concluded that there was no significant difference in treatment of syntax between G-A and G-ADV versions built to parse AdjAdvs. This result reinforces Radford (1988) argument that adjectives and adverbs belong to a single category.